Variables que afectan la relación entre las conductas sustentables y sus repercusiones psicológicas positivas: rasgos de personalidad y costos conductuales - Corral Verdugo, Víctor (Consorcio de Universidades Mexicanas A.C., 2020)
Sustainable behaviors (SB) can have both positive (wellbeing, satisfaction, happiness) and negative (costs, sacrifice) psychological impacts on people practicing such behaviors. This study investigated the possible influence of variables such as personality traits and behavioral costs on the relationship between SB and their positive psychological consequences. By using structural equations, a study of 100 college students at a northern Mexican city found higher levels of psychological benefits than behavioral costs associated with sustainable behaviors. The study also revealed that personality traits do not affect the SB-positive consequences relationship, while behavioral costs do have a negative impact on it, in a hybrid function, serving both as mediators and as moderators of the relationship.